Solid- and solution-state studies of the novel μ-dicyanamide-bridged dinuclear spin-crossover system {[Fe(bztpen)]2[μ-N(CN) 2]}(PF6)3·nH2O - Ortega-Villar, N; Thompson, A; Muñoz, M; Ugalde-Saldívar, V; Goeta, A; Moreno-Esparza, R; Real, J (2005)
The mononuclear diamagnetic compound {Fe(bztpen)[N(CN)2]} (PF6)CH3OH (1) (bztpen = N-benzyl-N,N′,N′- tris(2-pyridylmethyl)ethylenediamine) has been synthesized and its crystal structure studied. Complex 1 can be considered to be the formal pre-cursor of two new dinuclear, dicyanamide-bridged iron(II) complexes with the generic formula {[(Fe(bztpen)]2[μN(CN)2]}(PF6) 3·nH2O (n = 1 (2) or 0 (3)), which have been characterized in the solid state and in solution. In all three complexes, the iron atoms have a distorted [FeN6] octahedral coordination defined by a bztpen ligand and a terminal (1) or a bridging dicyanamide ligand (2 and 3). In the solid state, 2 and 3 can be considered to be molecu lar isomers that differ by the relative position of the phenyl ring of the two {Fe(bztpen)[N(CN)2]}+ halves (cis and trans, respectively). Depending on the texture of the sample, 2 exhibits para-magnetic behavior or displays a very incomplete spin transition at atmospheric pressure. Complex 3 undergoes a gradual two-step spin transition with no observed hysteresis in the solid state. Both steps are approximately 100 K wide, centered at ≈200 K and ≈ 350 K, with a plateau of approximately 80 K separating the transitions. The crystal structure of 3 has been determined in steps of approximately 50 K between 400 K and 90 K, which provides a fascinating insight into the structural behavior of the complex and the nature of the spin transition. Order-disorder transitions occur in the dicyanamide bridge and the PF6- ions simultaneously, with the spin-crossover behavior suggesting that these transitions may trigger the two-step character. In solution, 2 and 3 display very similar continuous spin conversions. Electrochemical studies of 2 and 3 show that the voltammograms are typical of dimeric systems with electronic coupling of the metals through the dicyanamide ligand. © 2005 Wiley-VCH Verlag GmbH and Co. KGaA, Weinheim.